Menekan Potensi Bulliying Di Sekolah Madrasah Aliyah Al Jamiatusysyubban Melalui Pendampingan Anti Bullying - M Ridwan; Rihatul Jannah; Ratna Dewi; Minhatul Ma’rif; Reni Suwenti (Jurnal Pengabdian Masyarakat, 2023)
To solve this problem requires a lot of involvement between parents, family and the school. Do not let this bullying become a habit and get used to it. It must be addressed and accompanied by many parties and all involved must immediately resolve this bullying problem. There needs to be a knowledge base so that students in Pandeglang feel safe when reporting and feel protected when they become victims. Seeing the many things that have happened, cases in Indonesia, especially in the character education school environment, need to be implemented and implemented, why is this it can happen either because of family factors, environmental factors or peer factors that can cause bullying to occur. an observation showing a research or education that is carried out in a planned, planned, sequential manner, and the objectives to be achieved in an observation are recorded all events and phenomena which are expressed in the results of observations, which are explained in detail, accurately, precisely, accurately, useful and objective matched the experimental observations. Implementation is the existence of an activity, action, action, or system mechanism that leads to the existence of not only an activity, but an activity planned and an activity carried out to achieve a goal.